Vegetables, fruits, and legumes: effect on urinary isoflavonoids phytoestrogen and lignan excretion - Hutchins, A M; Lampe, J W; Martini, M C; Campbell, D R; Slavin, J L (Journal of the American Dietetic Association, 1995)
Objective: To compare the effect of vegetable, fruit, and legume consumption on urinary isoflavonoid phytoestrogen and lignan excretion. Design: After 4 days of data collection, during which subjects consumed their habitual diets, subjects were randomly placed on four 9-day controlled experimental diets with each subject receiving each diet in a random order Subjects: Seven men and three women, aged 20 to 35 years, were recruited from the University of Minnesota Twin Cities community. Interventions: All subjects consumed four experimental diets in an assigned random order: a controlled basal diet, a legume/allium diet (containing garbanzo beans, garlic, and onions), and diets low or high in vegetables and fruits (containing apples, pears, potatoes, and carrots). Main outcome measures: Urine samples that were collected while subjects consumed their habitual diets and during the last 3 days of each feeding period were analyzed for isoflavonoid and lignan content using isotope dilution gas chromatography-mass spectrometry. Statistical analysis performed: The effect of vegetable and fruit intake on urinary isoflavonoid and lignan excretion was analyzed using the general linear model procedure. Post hoc comparisons were made using Duncan's multiple range test. Results: Subjects excreted more of the lignan enterodiol on the high vegetable/fruit diet compared with the basal and legume/allium diets (P = 0.03); more of the isoflavonoids O-desmethylangolensin (O-DMA), genistein, and sum of isoflavonoids on the legume/allium diet compared with the other controlled diets (P < 0.05); and more of the isoflavan equol on the basal and legume/allium diets compared with the high vegetable/fruit diet (P < 0.01). Subjects who excreted higher levels of equol on the basal and legume/allium diets also consumed more of the milk-based pudding provided as part of the controlled diets.